Aspects of treatment for posterior heel pain in young athletes - Thomas Elengard; Jón Karlsson; Karin Grävare Silbernagel (Dove Medical Press, 2010)
Thomas Elengard1, Jón Karlsson1, Karin Grävare Silbernagel21Department of Orthopaedics, Institute of Clinical Sciences at Sahlgrenska Academy, University of Gothenburg, Sahlgrenska University Hospital, Gothenburg, Sweden; 2Department of Mechanical Engineering, University of Delaware, Newark, Delaware, USAAbstract: Posterior heel pain occurs in young athletes involved in running and jumping. Due to the pain, the child often limits his/her physical activity level, with a possible negative effect on health and well-being. Although numerous research studies have examined the cause and treatment of heel and Achilles tendon pain in adults, there are no randomized clinical trials on treatment in children and adolescents. Therefore, there is limited evidence for how to treat young athletes with this type of complaint. The purpose of this review was to analyze critically and summarize the literature in regards to the cause and treatment of posterior heel pain in young athletes. The various diagnoses and clinical presentations relating to posterior heel and Achilles tendon pain are discussed. The theory and mechanism behind various recommended treatment strategies are also reviewed in the context of use in the young athlete. In summary, it is important to perform a thorough evaluation of each young athlete with heel pain to determine the appropriate diagnosis and to treat the deficits found and allow for a gradual progression to training. However, the recommendations at this time are based on clinical experience and a few retrospective studies, so further well designed prospective studies with validated outcome measures are urgently needed for the young athlete.Keywords: Sever's disease, apophysitis, tendinitis, tendinopathy, child, adolescent